USING FOLKTALES IN IMPLEMENTING TEXT-BASED APPROACH TO IMPROVE STUDENTS’ READING COMPREHENSION ABILITY - Edi Supriadi (ICoTE Proceedings)
This research is an ongoing research of using folktales in implementing text-based approach to improve students’ reading comprehension ability. The students' reading scores have been below or just slightly over the passing grades. The students have difficulties in completing the reading questions assigned by their teacher that range from scanning, skimming to inferring. As a result, the students' participation has been low and they show no interest in the lesson. To solve the problems, the writer will use folktales in implementing "Text-Based Approach" as the strategy to improve the students' Reading Comprehension Ability. Students are expected to be able to participate actively in the class and improve their reading comprehension ability. Activities applied in this research function to engage the students during the learning process which is indicated by their active contribution to the class discussion and interaction with peers and teachers.